2022
DOI: 10.3390/land11020184
|View full text |Cite
|
Sign up to set email alerts
|

Root Distribution and Soil Properties of Gully Heads and Their Effects on Headcut Migration in the Mollisols Region of Northeast China

Abstract: Previous studies have proved that root distribution along gully headwalls greatly alters soil properties and further affects the soil erodibility of gully heads. However, it is not clear whether the gully headcut migration is affected by root distribution and soil properties. Five representative gullies developed in different land uses were selected to clarify the variations of root distribution and soil properties and their effects on headcut migration in the rainy season (May to October 2021) in the Mollisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Our results found that planting grasses significantly improved soil physical structure and hence increased the resistance of soil erosion to runoff (Figure 4). Generally, the penetration of root systems can enhance soil porosity and infiltration capacity [5], which consequently increases the ANS of soil mass by altering the vertical migration of soil moisture and the lateral transport of surface runoff [39,51]. In this study, the soil ANS was positively related to soil TP with a power function (p < 0.05; Figure 6f).…”
Section: Response Of Soil Ans To Soil Propertiesmentioning
confidence: 52%
See 4 more Smart Citations
“…Our results found that planting grasses significantly improved soil physical structure and hence increased the resistance of soil erosion to runoff (Figure 4). Generally, the penetration of root systems can enhance soil porosity and infiltration capacity [5], which consequently increases the ANS of soil mass by altering the vertical migration of soil moisture and the lateral transport of surface runoff [39,51]. In this study, the soil ANS was positively related to soil TP with a power function (p < 0.05; Figure 6f).…”
Section: Response Of Soil Ans To Soil Propertiesmentioning
confidence: 52%
“…Soil erosion is a global problem that severely threatens agricultural production and the ecological environment [1,2]. It has caused surface fragmentation, vegetation degradation and soil loss and altered the regional geographic environment by changing the migration and deposition patterns of soil particles [3][4][5]. Overland flow is the main driving force of soil erosion, and soil anti-scourability (ANS) is an effective index that indicates the ability of soil to resist scouring by runoff [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations